Relative Prevalence and Associated Factors of Complex Regional Pain Syndrome Type I in Patients with Radial Head Fractures Treated with Open Reduction and Internal Fixation: A Cross-Sectional Study - Siming Jia; Chuan Ren; Xiaoying Shi; Tailong Shi; Dacheng Sun; Yuqin Zhang; Kai Ding; Hao Du; Yanbin Zhu; Wei Chen (Pain Research and Management)
Objective. This cross-sectional study aimed to examine the incidence and associated factors of complex regional pain syndrome type I (CRPS I) in patients who underwent open reduction and internal fixation (ORIF) for radial head fractures. Methods. The study enrolled 601 radial head fracture patients treated with ORIF, 523 of which completed the 1-year follow-up. The incidence of CRPS I in those patients was assessed using the Budapest criteria. Patients were then divided into 2 groups: patients with CRPS I (n = 28) and patients without CRPS I (n = 495). The patients’ demographic and clinical data before the operation were prospectively collected by our team. Independent t-tests and χ2 tests were used as univariate analyses to compare the demographic and clinical data between the two groups. Meanwhile, multivariate regression analysis was conducted to identify the associated risk factors for CRPS I. Results. The incidence of CRPS I in patients with radial head fractures treated with ORIF was 5.5% during the first year following surgery. Significant differences were observed in age, gender, type of trauma, modified Mason Classification, and depressive personality disorders. The logistic regression analysis revealed that the female gender, modified Mason type III fractures, and depressive patients were significantly more likely to develop CRPS I (p=0.021, 0.023, and 0.025, respectively). Conclusions. The incidence of CRPS I among radial head fracture patients undergoing ORIF was 5.5%. In addition, early detection of CRPS I and providing adequate intervention will likely result in greater benefits for those patients.